Response of Junior High School Students About Online Learning of PJOK Lessons in The Time of The Covid-19 Pandemic - Alam, Fikri Firmansyah; Maryanti, Rina (LPPM Universitas Jenderal Achmad Yani, 2022)
The purpose of this activity was to determine the responses of junior high school students to online learning of PJOK subjects during the covid 19 pandemic. This study used a qualitative descriptive method. Data collection techniques using online questionnaires. The questionnaire was distributed in the form of a google form link via WhatsApp Group. Observation respondents were 7th grade junior high school students as many as 20 students. The place where the observation was conducted was at SMPN 4 Bandung. Based on the results of student responses, most of the students gave a response that did not like the implementation of online learning of PJOK. Students' understanding of the material presented by the teacher during online learning is less understandable. Most of the student responses stated that online learning of PJOK was not fun because it was done alone at home and could not interact with teachers or friends, so students felt bored compared to offline learning PJOK. In overcoming the difficulties of online learning of PJOK, a more interactive online learning media is needed, so that the level of interaction between teachers and students online is the same as the level of student interaction offline.